The insider-outsider theory: a survey - Assar Lindbeck; Dennis J. Snower (Institute for the Study of Labor (IZA), 2002)
This article is an idiosyncratic survey of the insider-outsider theory, describing the vision underlying the theory, and evaluating salient contributions to the literature in the light of this vision. We also indicate what appear to have been dead-ends and red herrings in past research. The first section deals with the theory, concerning how labor turnover costs influence insider wages and outsiders? opportunities and how these costs affect employment and unemployment. We also address the more complex, and open, question of how employment and unemployment move through time, in response to labor market shocks. The second section deals with the insider-outsider theory in relation to two important economic institutions: unions and social norms. The third section confronts the relevant empirical evidence. Finally, the last section concludes by clarifying some common misunderstandings and identifying promising areas of future research.
Keywords: J68; J63; J64; J24; J23; J31; J42; J51; J38; J32; J41; 330; unemployment; wages; insiders; outsiders; social exclusion; labor turnover costs; unemployment persistence; employment; Insider-Outsider-Modell; Theorie